New Guinea an island apart (Sydney : BBC Enterprises Ltd., 1992)
Sixty million years ago, New Guinea was a a string of small islands in the middle of the Pacific. Then, as continents collided, it rose from the waters to become the largest tropical island in the world, ringed by coral reefs, capped by arctic-like tundra and glaciers, and devided by dramatic cascading rivers. It has been invaded by wildlife from all directions, giving the country the most unusual and dazzling diversity of animals and plants anywhere on earth
v.1. -Beyond the unknown shore v.2. Other worlds
backup available in VHS 1/2 in.
Keywords: Natural history -- New Guinea